Classification of environmental fragility in watershed using Fuzzy logic and AHP method - Lira, Karen Carrilho Silva; Francisco, Humberto Rodrigues; Feiden, Aldi (Sociedade & Natureza, 2022)
Assessment of environmental fragility in watersheds is an important tool to assist managers in planning and interventions for sustainable production and environmental conservation. The objective of this work was to use Fuzzy logic and the Analytic Hierarchy Process (AHP) method to classify environmental fragility using data obtained from public institutions. The Marreco River watershed in western Paraná, Brazil, was the study model. To classify areas, a geographic information system (GIS) and data from a digital elevation model (DEM), as well as data on soil occupation and type were used. The analysis found that 71.3% of the basin area has average fragility. Compared to two other forms of weighing elements of the slope map, the three presented statistical difference, but all indicated that the basin under study mostly has average environmental fragility. The use of fuzzy logic allowed application of a continuous variation of weights according to the variation of environmental characteristics, which may more effectively represent the reality and, therefore, provide more reliable results. This method may represent a useful tool to appropriately manage sustainable production and environmental conservation in watershed areas.